Reward, Perceived Organizational and Supervisor Support (POS), Work Life Balance sebagai Faktor Kinerja Karyawan melalui Employee Engagement - Tri Wahyu Nurcahyo (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
The purpose of this research is to analyze the effect of reward, Perceived Organization and Supervisor Support (POS) and work-life balance on employee performance through employee engagement. The number of respondents in this study amounted to 75 respondents with purposive sampling technique. This study uses a quantitative approach using SPSS data analysis. Based on the results of the analysis, it can be concluded that there is a simultaneous influence between reward, Perceived Organization and Supervisor Support (POS) and work-life balance on employee performance through employee engagement. Keywords: employee performance, reward, perceived organization and supervisor support (POS), work-life balance, employee engagement